Long non-coding RNAs as novel therapeutic targets in juvenile myelomonocytic leukemia - Hofmans, Mattias; Lammens, Tim; Depreter, Barbara; Wu, Ying; Erlacher, Miriam; Caye, Aurélie; Cavé, Hélène; Flotho, Christian; de Haas, Valerie; Niemeyer, Charlotte M.; Stary, Jan; Van Nieuwerburgh, Filip; et al. (Scientific reports, 2021)
Juvenile myelomonocytic leukemia (JMML) treatment primarily relies on hematopoietic stem cell transplantation and results in long-term overall survival of 50–60%, demonstrating a need to develop novel treatments. Dysregulation of the non-coding RNA transcriptome has been demonstrated before in this rare and unique disorder of early childhood. In this study, we investigated the therapeutic potential of targeting overexpressed long non-coding RNAs (lncRNAs) in JMML. Total RNA sequencing of bone marrow and peripheral blood mononuclear cell preparations from 19 untreated JMML patients and three healthy children revealed 185 differentially expressed lncRNA genes (131 up- and 54 downregulated). LNA GapmeRs were designed for 10 overexpressed and validated lncRNAs. Molecular knockdown (≥ 70% compared to mock control) after 24 h of incubation was observed with two or more independent GapmeRs in 6 of them. For three lncRNAs ( lnc-THADA-4 , lnc-ACOT9-1 and NRIR ) knockdown resulted in a significant decrease of cell viability after 72 h of incubation in primary cultures of JMML mononuclear cells, respectively. Importantly, the extent of cellular damage correlated with the expression level of the lncRNA of interest. In conclusion, we demonstrated in primary JMML cell cultures that knockdown of overexpressed lncRNAs such as lnc-THADA-4 , lnc-ACOT9-1 and NRIR may be a feasible therapeutic strategy.